The Opportunity Cost of Electricity Outages and Privatization of Substations in Nepal - Roop Jyoti; Aygul Ozbafli; Glenn Jenkins (Queen's University, Department of Economics, 2006)
The unreliability of electricity supplies is a major cause of the high cost of manufacturing in developing countries. In this paper, we are able to measure the cost imposed by power outages and suggest some feasible mitigating measures. The study employs a rich, if not unique, set of data from three large manufacturing enterprises in Nepal. Using it, the opportunity costs to the enterprises from lost production from electricity outages can be estimated accurately. Power outages due to substation failure can be separated from other electricity systems failures. An analysis is carried out on the feasibility of privatized electricity substations. We find that this is a very worthwhile capital investment for the private sector to undertake, even when additional generation capacity to improve overall electricity reliability is not justified.
Keywords: L94; Q41; Q48; 330; electricity supply; reliability; opportunity costs; privatization